Acrylamide in Foods: A Review and Update - Amy H. Simonne; Douglas L. Archer (EDIS, 2002)
This document is FCS8759, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: October, 2002.